Nano/Micro Metal‐Organic Framework‐Derived Porous Carbon with Rich Nitrogen Sites as Efficient Iodine Hosts for Aqueous Zinc‐Iodine Batteries - Yong Li; Xiaotian Guo; Shixian Wang; Wenzhuo Sun; Dianheng Yu; Nana Li; Huijie Zhou; Xiaoxing Zhang; Huan Pang (Advanced Science)
Abstract Nowadays, the low cost, superior safety, and long durability of aqueous zinc–iodine (Zn–I2) batteries have garnered significant interest. Nevertheless, their practical use is limited by the inferior conductivity of iodine and the shuttle effect, resulting in suboptimal electrochemical behavior. In this work, a nano/micro zinc‐based metal‐organic framework (Zn‐MOF) featuring a cubic morphology is employed for obtaining porous nitrogen‐doped carbon (NC), which is reported as a cathode host for Zn–I2 batteries. Thanks to its porous architecture and high conductivity of NC, the optimized S3‐1000 material achieves high iodine loading and enables rapid electron/ion transport. More importantly, the adsorption experiments combined with density functional theory (DFT) calculations reveal that the graphitic‐N and pyridine‐N moieties within the carbon matrix synergistically serve as active anchoring sites for iodine species, suppress polyiodide shuttle effects and accelerate redox kinetics during iodine conversion. As a result, the I2@S3‐1000 cathode achieves the highest specific capacity and superior cycle stability over 10,000 cycles, while in‐situ characterization analysis confirms the reversible electrochemical mechanism. Soft pack battery and prototype flexible micro‐battery based on the I2@S3‐1000 cathode are also fabricated and show excellent flexibility. This study promotes the development of MOF‐derived carbon as iodine cathodes for advanced Zn–I2 batteries.